1975
DOI: 10.1128/jb.122.2.526-531.1975
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of tyrosine isoaccepting transfer ribonucleic acid species in wild-type and asporogenous strains of Bacillus subtilis

Abstract: The relative amounts of two isoacceping species of tyrosine transfer ribonucleic acid, tRNATyrI and tRNATyrII, determined from reversed phase 5 profiles of tyrosyl-tRNA, prepared from Bacillus subtilis strain W168, were growth phase and medium dependent. The growth phase-dependent alterations in the relative amounts of tRNATyr species were also demonstrated in 11 asporogenous strains of B. subtilis. The proportion of tRNA-Tyr species and the extent of the alteration in their relative amounts during the transit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
0

Year Published

1976
1976
1983
1983

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…(i) Growth rate. It has been reported that the composition of the growth medium affects the tyrosyl-tRNA pattern of B. subtilis (17). We thus determined the ratio of species I and II in tRNA extracted from cells cultivated in media, allowing different growth rates and different sporulation frequencies.…”
Section: Fraction Numbermentioning
confidence: 99%
See 2 more Smart Citations
“…(i) Growth rate. It has been reported that the composition of the growth medium affects the tyrosyl-tRNA pattern of B. subtilis (17). We thus determined the ratio of species I and II in tRNA extracted from cells cultivated in media, allowing different growth rates and different sporulation frequencies.…”
Section: Fraction Numbermentioning
confidence: 99%
“…The modification of B. subtilis tRNAIYr first reported by Arceneaux and Sueoka (1) for cells grown in a complex medium, consists of a reversal in the relative amounts of the two major species, tRNAIYr I being predominant in vegetative cells and tRNATvr II in stationaryphase cells and spores. McMillian and Arceneaux (17) extended this study by comparing tRNAT'r patterns of a wild-type strain grown in various media and of asporogenous mutants. According to this analysis, the extent of tRNATrr modification does not seem to be directly correlated with the ability of cells to sporulate.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Bacillus subtilis tRNATcan be separated by chromatography into two major species. One of these (tRNATyI) is predominant in vegetative cells, whereas the other (tRNATYIII) is the major component in stationary-phase cells and spores (1,10,12,18). tRNAT-" modification begins during the last division of exponential growth phase and is over by 2 h after the end of this phase.…”
mentioning
confidence: 99%
“…Investigations of mechanisms controlling bacterial spore development have involved an intense examination of the regulatory role that tRNA may play in this system (18,20,21,35). Sporulation in Bacillus subtilis is accompanied by significant qualitative and quantitative changes in at least eight iso-accepting tRNA species (37).…”
mentioning
confidence: 99%